PERANCANGAN PROTOTYPE SMART HOME MENGGUNAKAN MIKROKONTROLER ESP32 BERBASIS IOT DAN TELEGRAM - Yosua, Lucky; Rino (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2024)
Smarthome is a combination of internet of things (IoT). The use of a smarthome controlled using telegram functions to provide better comfort, provide efficiency in activities and save on electrical energy use. That way, there will be no more forgetting to turn off the AC or turning on or off the lights, watering house plants and forgetting to lock the door because by using a Smarthome device at home or in an office building, electrical equipment will be drained. able to work automatically according to user needs. Users can also control electrical devices indoors and outdoors using communication channels such as via the internet network. The aim of creating this smarthome is to provide better comfort, make it easier to control home electronic devices so that activities become more efficient. The development model used in this research is design to look for research that is similar to the tools that will be used then analysis to study things related to the research after that design to make a miniature room as clear as possible and implementation aims to examine and find out each whether each system is functioning as desired or whether an error has occurred. Based on the results of system testing, it can be concluded that the tool can work as expected.